Face-to-face Learning in Primary School during Pandemic: Kampus Mengajar Perintis Practice - Agung Santika; Atika Nur Hidayah; Nanda Defiana (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2021)
Kampus Mengajar Perintis (KMP) is a part of programs released by the Ministry of Education of Republic Indonesia. The program aims to call higher education students in assisting primary schools with lowest national institution accreditation in teaching and learning, administration and technological adaptation during the COVID-19 pandemic. Through the program, primary schools in Indonesia have started to conduct face-to-face learning, even in a very limited time. Some schools preferred to run face-to-face learning at school but others chose a home visit mode, or even combined the both. The present study observed the practices of face-to-face teaching and learning in one of primary school in Central Java where KMP participants involved in. The finding shows that KMP students together with the teachers created several activities for starting the learning and teaching again after more than one year doing online learning.